Feeding ecology analysis of sand lobsters (Panulirus homarus) - Lubis, Amelia Sriwahyuni; Efrizal, Efrizal; Syaifullah, Syaifullah (Universitas Malikussaleh, 2024)
This research is scheduled to take place from May to August 2022 at the Marine and Brackish Water Aquaculture Fisheries Center in West Sumatra. The method employed will be observation, which entails monitoring the eating behavior of lobsters and their feeding schedule every time food is provided within a 24-hour timeframe. Data pertaining to lobster eating behavior will be analyzed descriptively based on these observations. Throughout the research, various feeding activities of sand lobsters were documented. The observational results indicated that the lobster feeding process remained consistent. The lobster typically initiates the process by gripping the food with its claws and feet, subsequently breaking it into smaller pieces with its claws, and then placing these fragments into its mouth. As the lobster tears apart the food, the next step involves transferring it to the mouth using the nearest upper and lower jaws. In light of this research, it can be inferred that lobster feeding behavior encompasses the following steps: firstly, the lobster approaches the food after spotting it; secondly, lobsters employ their claws to grasp the food; and finally, lobsters tear and ingest the food. Lobster feeding activities are most commonly observed between 6:00 PM - 10:00 PM and 10:00 PM - 2:00 AM.Keywords: eating behavior; lobster; Lobster feeding schedule.